Ex vivo and in vivo evidence that cigarette smoke-exposed T regulatory cells impair host immunity against Mycobacterium tuberculosis - Bai, Xiyuan; Verma, Deepshikha; Garcia, Cindy; Musheyev, Ariel; Kim, Kevin; Fornis, Lorelenn; Griffith, David E.; Li, Li; Whittel, Nicholas; Gadwa, Jacob; Ohanjanyan, Tamara; Eggleston, Matthew J.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction A strong epidemiologic link exists between cigarette smoke (CS) exposure and susceptibility to tuberculosis (TB). Macrophage and murine studies showed that CS and nicotine impair host-protective immune cells against Mycobacterium tuberculosis (MTB) infection. While CS and nicotine may activate T regulatory cells (Tregs), little is known about how CS may affect these immunosuppressive cells with MTB infection. Methods We investigated whether CS-exposed Tregs could exacerbate MTB infection in co-culture with human macrophages and in recipient mice that underwent adoptive transfer of Tregs from donor CS-exposed mice. Results We found that exposure of primary human Tregs to CS extract impaired the ability of unexposed human macrophages to control an MTB infection by inhibiting phagosome-lysosome fusion and autophagosome formation. Neutralizing CTLA-4 on the CS extract-exposed Tregs abrogated the impaired control of MTB infection in the macrophage and Treg co-cultures. In Foxp3+GFP+DTR+ (Thy1.2) mice depleted of endogenous Tregs, adoptive transfer of Tregs from donor CS-exposed B6.PL(Thy1.1) mice with subsequent MTB infection of the Thy1.2 mice resulted in a greater burden of MTB in the lungs and spleens than those that received Tregs from air-exposed mice. Mice that received Tregs from donor CS-exposed mice and infected with MTB had modest but significantly reduced numbers of interleukin-12-positive dendritic cells and interferon-gamma-positive CD4+ T cells in the lungs, and an increased number of total programmed cell death protein-1 (PD-1) positive CD4+ T cells in both the lungs and spleens. Discussion Previous studies demonstrated that CS impairs macrophages and host-protective T effector cells in controlling MTB infection. We now show that CS-exposed Tregs can also impair control of MTB in co-culture with macrophages and in a murine model.